2011
DOI: 10.5740/jaoacint.9-493
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric Determination of Some Water-Soluble Vitamins

Abstract: Two simple and sensitive spectrofluorimetric methods were developed for determination of three water-soluble vitamins (B1, B2, and B6) in mixtures in the presence of cyanocobalamin. The first one was for thiamine determination, which depends on the oxidation of thiamine HCl to thiochrome by iodine in an alkaline medium. The method was applied accurately to determine thiamine in binary, ternary, and quaternary mixtures with pyridoxine HCl, riboflavin, and cyanocobalamin without interference. In the second metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…16 Moreover, advanced chemometic techniques were recently applied to vitamin mixtures to mathematically resolved UV−vis spectra of fat-and water-soluble vitamins. 17,18 It should be mentioned that the common disadvantages of existing methods for vitamin analysis include time-consuming sample preparation (e.g., extraction) to remove endogenous interferences from the matrix, high solvent volume, demand of complex multivariate methods, or the necessity of supercritical conditions to cover all vitamin ranges in a single analytical run. 17−19 Apart from active ingredients (vitamins), a number of accompanying substances (sweeteners, acidifiers, and antioxidant agents) can be found in multivitamin preparations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Moreover, advanced chemometic techniques were recently applied to vitamin mixtures to mathematically resolved UV−vis spectra of fat-and water-soluble vitamins. 17,18 It should be mentioned that the common disadvantages of existing methods for vitamin analysis include time-consuming sample preparation (e.g., extraction) to remove endogenous interferences from the matrix, high solvent volume, demand of complex multivariate methods, or the necessity of supercritical conditions to cover all vitamin ranges in a single analytical run. 17−19 Apart from active ingredients (vitamins), a number of accompanying substances (sweeteners, acidifiers, and antioxidant agents) can be found in multivitamin preparations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is extensively used as a component of single vitamin B complex and multivitamin preparations [2][3][4]. Several analytical methods, including UV and visible spectrophotometric and multivariate analysis [5][6][7], fluorimetric [8][9][10][11][12][13][14][15][16][17][18][19][20][21], high performance liquid chromatography (HPLC) [22][23][24][25][26][27][28][29][30][31][32][33][34][35], UHPLC/MS-MS [36], turbidimetric and nephelometric [37], amperometric [38], and voltammetric methods [39][40][41][42][43][44][45], have been used for the assay of thiamine and its salts in pharmaceutical preparations, food materials and biological fluids. Some of these methods have previously been reviewed [46][47][48]…”
Section: Introductionmentioning
confidence: 99%
“…iamine undergoes chemical [1,8,9,11,14,16,17,19,[51][52][53][54] and photochemical oxidation [55,56] to form thiochrome (TC) which exhibits a blue fluorescence (440 nm). is has been made as the basis of fluorimetric determination of TH [8,9,11,14,16,17,19,[54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…For example Khan [15] found the linear range from 0.026-16.830 µg/mL, r = 0.9964, RSD = 1.75%, LOD = 0.015 µg/mL, Mohamed [16] found that linear range from 10-500 ng/mL , r = 0.9991, RSD = 0.46-1.02%, Recovery = 97.6% and Szpikowska-Sroka [17] found the linear range from 0.4-2.4 µg/mL , r = 0.9998 and LOD = 0.19 and 0.26 µg/mL. 0.9998 * y = a + bx; y: the transmittance of concentration, x: the concentration in µg/mL.…”
Section: Selectivitymentioning
confidence: 99%
“…Two simple and sensitive spectrofluorimetric methods were developed for determination of thiamine by oxidized to thiochrome by iodine in an alkaline medium [16] or oxidized with potassium iodate(V) to the colourless product and a stoichiometric amount of iodide ions was formed. The latter reacted with the excess of iodate(V) ions in acidic medium, to form free iodine which oxidized leucocrystal violet to the crystal violet dye [17].…”
Section: Introductionmentioning
confidence: 99%